Delayed diagnosis of hypopituitarism following severe traumatic brain injury - Kolli, Sreedhar (BMJ Publishing Group, 2010)
The following case illustrates a 10-year delay in the diagnosis of hypopituitarism after severe traumatic brain injury in a 22-year-old man crushed by a forklift truck. His symptoms of mood changes, headaches and sleep pattern disturbances were attributed to post traumatic brain injury syndrome resulting in a delay in diagnosing the underlying pathology. Following recurrent episodes of symptomatic hyponatraemia, hypopituitarism was diagnosed. When pituitary hormone replacement treatment was given, there was clinical and biochemical improvement. There is currently very limited evidence in the literature to routinely screen patients post traumatic brain injury for pituitary dysfunction.